If you give a girl a bike - Diep, Hayley (Hayley Diep, 2021)
"If you give a girl a bike, she will ride and ride and ride. She may also ask for a skateboard, climbing shoes, and a surfboard! Follow these adventurous girls as they learn new sports. They may fall every now and then, but they aren't afraid of a few scapes or bruises!"--Back cover.